SITUS HINDU PRA-ISLAM: MENCARI TITIK TEMU ANTARA TOLERAN ATAU INTOLERAN SUNAN KUDUS DAN GENERASI MUSLIM KUDUS - Rosyid, Moh; Kushidayati, Lina (JURNAL ISLAM NUSANTARA, 2021)
This study aims to explain that ancient buildings inherited by Hindus in pre-Islamic Kudus have been preserved until now as a form of tolerance that needs to be studied. This study uses a qualitative approach to the type of field. The data collection technique is done through interviews, observation, and literature deepening. The results showed that the Kudus City of Central Java has a specific site, namely the Langgar Bubrah building, in which there are phallus and yoni as temple characters. However, the perfect name of the building to be immortalized is Sanggar Bubrah, not Langgar Bubrah. Likewise, at the building point of the Al-Aqsa Mosque, Menara Kudus, there was a pure with evidence of two kori (pure entrances) in the foyer and inside Al-Aqsa Mosque. Sunan Kudus forbids Muslims from slaughtering cows (as a tribute to Hindus) which is still preserved today.